VIKSIT BHARAT : A ROAD AHEAD - Chopra, Rajiv; Pandey, Srikant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Viksit Bharat@2047 outlines a bold and broad qualitative/ transformative roadmap for India’s development by its 100th year of independence. This vision emphasizes a balanced approach integrating economic strength, social inclusion, and environmental sustainability. Key pillars include promoting innovation in technology, entrepreneurship, and skill development to build a knowledge-driven economy. It prioritizes renewable energy, climate resilience, and eco-friendly practices to ensure sustainable growth. The initiative also lays emphasis on good governance, transparency, and international cooperation to address global and local challenges. With a strong focus on inclusive growth, it seeks to uplift marginalized groups, empower youth, and reduce inequality, positioning India as a leader in equitable and sustainable development.